Transforming medical education in Liberia through an international community of inquiry - Kristina Talbert-Slagle; Ibrahim Ajami; Braden Currey; Rachel Galvao; Jerusalem Hadush; Serene Silin Li; Javaughn T. Flowers; Moses Ziah; Desmond Amuh; Mikaela Rabb; Olayinka Stephen Ilesanmi; Nikole Allen; et al. (Public Library of Science (PLoS), 2023)
A critical component of building capacity in Liberia's physician workforce involves strengthening the country's only medical school, A.M. Dogliotti School of Medicine. Beginning in 2015, senior health sector stakeholders in Liberia invited faculty and staff from U.S. academic institutions and non-governmental organizations to partner with them on improving undergraduate medical education in Liberia. Over the subsequent six years, the members of this partnership came together through an iterative, mutual-learning process and created what William Torbert et al describe as a "community of inquiry," in which practitioners and researchers pair action and inquiry toward evidence-informed practice and organizational transformation. Incorporating faculty, practitioners, and students from Liberia and the U.S., the community of inquiry consistently focused on following the vision, goals, and priorities of leadership in Liberia, irrespective of funding source or institutional affiliation. The work of the community of inquiry has incorporated multiple mixed methods assessments, stakeholder discussions, strategic planning, and collaborative self-reflection, resulting in transformation of medical education in Liberia. We suggest that the community of inquiry approach reported here can serve as a model for others seeking to form sustainable global health partnerships focused on organizational transformation.